2002
DOI: 10.1093/emboj/cdf650
|View full text |Cite
|
Sign up to set email alerts
|

Mlc1p promotes septum closure during cytokinesis via the IQ motifs of the vesicle motor Myo2p

Abstract: Little is known about the molecular machinery that directs secretory vesicles to the site of cell separation during cytokinesis. We show that in Saccharomyces cerevisiae, the class V myosin Myo2p and the Rab/Ypt Sec4p, that are required for vesicle polarization processes at all stages of the cell cycle, form a complex with each other and with a myosin light chain, Mlc1p, that is required for actomyosin ring assembly and cytokinesis. Mlc1p travels on secretory vesicles and forms a complex(es) with Myo2p and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(128 citation statements)
references
References 54 publications
(104 reference statements)
7
120
1
Order By: Relevance
“…To determine whether or not Shs1 exerts a distinct function from other septins in septin ring assembly and/or cytokinesis, we constructed shs1D cells in the W303 background. Proper disruption of SHS1 was verified by PCR (data not Wagner et al (2002) shown). The shs1D cells grew slowly at 25°and did not grow at 20° (Figure 1A).…”
Section: Resultsmentioning
confidence: 98%
“…To determine whether or not Shs1 exerts a distinct function from other septins in septin ring assembly and/or cytokinesis, we constructed shs1D cells in the W303 background. Proper disruption of SHS1 was verified by PCR (data not Wagner et al (2002) shown). The shs1D cells grew slowly at 25°and did not grow at 20° (Figure 1A).…”
Section: Resultsmentioning
confidence: 98%
“…Required for Myo1 targeting to the division site during cytokinesis, required for Iqg1 localization to the division site, and thus required for AMR assembly [Stevens and Davis, 1998;Boyne et al, 2000;Shannon and Li, 2000;Wagner et al, 2002;Luo et al, 2004;Fang et al, 2010] …”
Section: Mlc1mentioning
confidence: 99%
“…Catalytic subunit of chitin synthase III Required for the synthesis of chitin in the ''bud scar'' and the cell wall and may also play a role in SS formation [Shaw et al, 1991;Chuang and Schekman, 1996 [Kovacech et al, 1996] Chs1 Chitin synthase I Involved in septum repair at low pH after cell separation [Cabib et al, 1989;Cabib et al, 1992] Coordination of actomyosin ring and primary septum formation Septins GTP-binding and filament-forming proteins Required for AMR assembly and PS formation [Hartwell, 1971;Longtine et al, 1996 (p 297);Mino et al, 1998;Takizawa et al, 2000;Roh et al, 2002;Dobbelaere and Barral, 2004] Mlc1 ELC Required for AMR assembly and PS formation [Stevens and Davis, 1998;Boyne et al, 2000;Shannon and Li, 2000;Wagner et al, 2002;Luo et al, 2004;Fang et al, 2010] Iqg1 IQGAP Required for AMR assembly and PS formation [Epp and Chant, 1997;Shannon and Li, 1999;Boyne et al, 2000;Korinek et al, 2000;Ko et al, 2007;Tully et al, 2009;Fang et al, 2010] (Continued) n 720…”
Section: Chs3mentioning
confidence: 99%
“…We hypothesized that the association of Myo2p with the accumulated post-Golgi vesicles in some late sec mutants (Wagner et al, 2002) might interfere with the localization of the myosin in these cells. To avoid this, we also examined cable and Myo2p distribution in yeast bearing conditional blocks in earlier steps of the secretory pathway.…”
Section: Polarized Secretion Maintains Cable Assembly Activity At Thementioning
confidence: 99%
“…However, this interpretation is complicated in that for many of these sec mutants, the overall localization of Myo2p was very poor, yet Myo2p itself is required to maintain cable assembly activity at the bud cortex. Thus, it was possible that in these mutants, the loss of bud cortex-associated cables was an indirect effect of delocalizing Myo2p.We hypothesized that the association of Myo2p with the accumulated post-Golgi vesicles in some late sec mutants (Wagner et al, 2002) might interfere with the localization of the myosin in these cells. To avoid this, we also examined cable and Myo2p distribution in yeast bearing conditional blocks in earlier steps of the secretory pathway.…”
mentioning
confidence: 99%